Antibiotic prophylaxis and its appropriate timing for urological surgical procedures in patients with asymptomatic bacteriuria: A systematic review - Ramos, Jorge A. (Arab J Urol, 2016)
OBJECTIVE: To review the existing literature on when and how to treat patients with asymptomatic bacteriuria (AB) who undergo urological surgery, as uncertainty about this issue persists. METHODS: A systematic review was conducted to compare the different timing of administration of antibiotic prophylaxis in patients with AB undergoing urological surgery. We used predefined inclusion and exclusion criteria, and we also developed a specific quality scale to assess the quality of the papers included. RESULTS: Nine studies met the inclusion criteria. Of the nine studies included, eight evaluated antibiotic prophylaxis regardless of the presence of AB, as their purpose was to evaluate the effectiveness of antibiotic prophylaxis for urological procedures. Of these, four studies showed a significant reduction in the rate of infections in the intervention group compared with placebo, or with the same antibiotic therapy but using different durations of therapy. Four studies found no significant differences in infectious complications between the intervention and comparison arms. Only one study assessed the duration of antibiotic prophylaxis in patients with AB. CONCLUSIONS: With the available evidence, antibiotic therapy should be considered only for procedures in which studies have shown a clinical benefit in the prevention of infection. It is important to establish the duration and type of treatment for antimicrobial therapy for surgical prophylaxis in patients with AB who are going to receive urological invasive procedures.